Stabilization of a specific nuclear mRNA precursor by thyroid hormone. - Narayan, P (1985)
The regulation of a thyroid hormone-responsive gene in rats, designated spot 14, was explored. The expression of this gene in liver is rapidly (less than 10 min) and markedly (greater than 10-fold) altered by the administration of 3,5,3'-triiodo-L-thyronine (T3) to hypothyroid rats (P. Narayan, C. W. Liaw, and H. C. Towle, Proc. Natl. Acad. Sci. USA 81:4687-4691, 1984). To investigate the cellular site at which T3 acts to induce this hepatic mRNA, we made parallel measurements of the relative levels of spot 14 mRNA and nuclear precursor RNA and of the rate of gene transcription after treatments designed to alter the thyroid status of rats. The relative levels of both the mRNA and nuclear precursor were elevated roughly 5- to 6-fold in euthyroid animals and 9- to 12-fold in hyperthyroid animals over those in hypothyroid controls. However, only a small difference of approximately 1.5-fold was detected in the rate of spot 14 gene transcription. After a single injection of T3 into hypothyroid animals, a small and transient rise in the transcription rate was detected at 30 min. However, the levels of spot 14 mRNA and nuclear precursor RNA increased much more dramatically throughout the first 4 h of treatment. In both cases, changes in the rate of gene transcription were not capable of accounting for the alterations observed in mRNA levels. Thus, the major site of spot 14 gene regulation by T3 is at a posttranscriptional level. The proportional changes observed in the nuclear precursor and mRNA levels suggest that the site of control is at the level of stability of the nuclear precursor RNA for spot 14 mRNA.